From Bottle to Tap: A Systematic Review of Interventions That Shift Beverage Intake from Sugar-Sweetened and Bottled Drinks to Tap Water - Dudiyanto Pakaya; Fitriyane Lihawa; Dewi Wahyuni K Baderan (West Science Interdisciplinary Studies, 2025)
Rising consumption of bottled water and sugar-sweetened beverages poses challenges for health, environmental sustainability, and equity in access to safe drinking water. This systematic review examines interventions promoting a shift from bottled drinks to tap or plain water, focusing on behavioral mechanisms and impacts on health, nutrition, and the environment. Studies reviewed included diverse settings and methodologies, assessing outcomes related to beverage intake and associated indicators. Successful interventions combined infrastructure improvements, such as hydration stations, with education and policy changes favoring tap water. Behavioral responses were influenced by perceptions of safety and taste, while socio-economic and demographic factors affected effectiveness. Interventions generally led to reduced consumption of sugar-sweetened beverages and increased tap-water intake, with evidence of improved health outcomes in high-risk populations. Modelling studies anticipated significant reductions in greenhouse gas emissions and resource use by substituting tap water for bottled beverages. The review concludes that well-designed interventions can foster healthier beverage systems but calls for longer-term assessments that encompass health, environmental, and equity outcomes.